Zenker Diverticulum - Adelien Adelien (HM Publisher, 2021)
Zenker Diverticulum is a multifactorial disorder of the Killian’s triangle in thehypopharynx characterized by the main symptoms of dysphagia affecting theseventh and eighth decades of age and rarely under 40 years of age. The existenceof factors that cause an increase in the intraluminal pressure of the pharynx willlead to the formation of a pocket located in the Killian’s triangle, an area with weakertone of the hypopharyngeal wall and a decrease in relative pressure in theretropharyngeal space. Zenker Diverticulum was first described by Ludlow in 1769,who reported abnormal dilatation of the posterior pharyngeal wall on postmortemexamination of a patient who complained a lifelong dysphagia. Zenker Diverticulumis thought to be associated with increasing age in relation to motor musclecoordination for swallowing functions and GERD (gastroesophageal reflux disease).Symptoms include dysphagia, regurgitation, malnutrition, and recurrent aspirationpneumonia. Management includes invasive surgery and non-invasive endoscopy.